Dual polarized UHF antenna - MIESLINGER STEFAN; KOBER MICHAEL; MENKE NORBERT WILHELM (2014)
Described are antenna assemblies and methods for forming antenna assemblies. An antenna assembly includes a dual polarized far-field antenna and a near-field loop antenna. The near-field loop antenna is electromagnetically coupled to the dual polarized far-field antenna. The near-field loop antenna includes two contacts for electrically connecting to a chip.